The Contribution of Customer Satisfaction towards Company Image and its impact in Revolution Industry 4.0 Era - Samsurijal Hasan; Citrawati Jatiningrum; Miswan Gumanti (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study focus on the crucial factors with the development of the workflows for enhancing the corporate images in the public company. Design/methodology/approach: The reviews were quantitative studies using three primary data (i.e., Observation, Questioners, and Interviews) with followed by data analysis and model with the workflow determination. Findings: The result shows company image variable is positively influenced by customer satisfaction variable. Also, the Quality of service reach the level of excellence expected and meet customer needs. The Quality of service becoming very important due to its understanding market and customer needs to and the product or services which should be given by the company. Quality of service is the crucial factor for a company to sustainable and make quality improvements in processing, packaging, and distributing for better company images. Research limitations/implications: Although, the Regional Water Management Company (PDAM) as a local monopoly company providing water for society, improvements in service need to be implemented for enhanced the company images. They should be developing to improve public services, in terms of qualities that qualify as clean water and quantity in the sense that more communities can be served. Practical implications: Therefore, it is necessary that the implementation of quality control management is planned, and implemented systematically and continuously, for the stability of the company. Originality/value: This paper is originality Paper type: Research paper